Predictors of generation Z revisit intention to Mangkokku Restaurant during COVID-19 pandemic - Budi Suyanto; Kevin G. Yulius; Julita; Sundring P. Djati; Nurbaeti (Enrichment : Journal of Management, 2023)
Revisit Intention in service industry especially in a tourism related business is considered as the catalyst of growth. During the COVID-19 pandemic, a lot of restaurants and other food and beverage service-related business experiencing a decrease in visitation. This research was conducted to identifying factors that might influence revisit intention to Mangkokku, a restaurant specializing selling rice bowl with Indonesian twist. Generation Z was chosen as the subject as their number keep growing. Five hypotheses were proposed with five independent variables, food quality, service quality, atmospherics, other customers and perceived value. Online questionnaires were distributed to 170 respondents and data analysis was carried out with IBM SPSS 25. The instrument was valid and reliable, but the partial hypothesis test had a very distinctive result. Perceived value was the only independent variable able to influence revisit intention to Mangkokku significantly. Future research must consider other factors and using a longitudinal data series for a more representative result. Restaurant owner must consider the unique value and view of Generation Z as they are the future of the service industry.